The Effectiveness of Self-Directed Learning for English Language Education: A Systematic Literature Review - Fadhilah Ramadhanty; Dasuki Dasuki; Dewinta Mandalika; Sri Sumarni (Universitas Muhammadiyah Semarang, 2023)
Self-directed learning is a method of education in which students are in charge of their education. Self-directed learners take the initiative to determine their learning requirements, establish learning objectives, and create and carry out learning plans. To determine the potential and efficacy of self-directed learning in English language education, the goal of this research is to present and analyze the features of self-directed learning in English language education. This systematic literature review conducted 15 papers published between 2015 and 2023 that were accepted for this investigation by the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) guidelines. The results of this study suggest that self-directed learning offers significant learning potential for students. Students can plan their time accordingly. The result highlights the need for an all-encompassing educational strategy to improve student's abilities in a variety of areas, including English subject objectives like self-directed learning. The process of self-directed learning depends on motivation.